PENGARUH LOCUS OF CONTROL DAN KOMITMEN PROFESI TERHADAP PERILAKU AUDITOR PADA SITUASI KONFLIK AUDIT PADA KANTOR AKUNTAN PUBLIK KOTA MEDAN - Mas ut; Zahidun Safaruddin (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2020)
The purpose of this study is to determine the interaction of locus of control personality variables and professi commitment to auditor behavior in an audit conflict situation that is the auditor's ability to survive or justify client pressure. This study uses primary data that is data taken directly from respondents with a questionnaire technique to 65 auditors from several public accounting firms in the city of Medan. Data were analyzed using multiple linear regression. The results of this study stated that partially the locus of control variable had no effect and was not significant to the auditor's behavior in an audit conflict situation, the variable of professi commitment had a negative and significant effect on the auditor's behavior variable in an audit conflict situation, and the locus of control and professi commitment had an effect simultaneous of the auditor's behavior in an audit conflict situation.